Association of the modified Balance Error Scoring System during the off-season with a history of sports-related concussion in professional soccer players - Hirano, Atsushi; Takei, Shunji; Yaguchi, Toru; Imoo, Yoshiyuki; Kobayashi, Hiroyuki; Tobita, Kodai; Yoshida, Kohei; Uchida, Takuro; Aoto, Katsuya (Japanese Journal of Sports Physical Therapy, 2024)
Objective: The modified Balance Error Scoring System (mBESS) is the most widely used method for simple assessment of postural control immediately after a sports-related concussion. On the other hand, there have been few studies on the effects of previous concussions on postural control in Japan. Therefore, the purpose of this study was to investigate the relationship between concussion and mBESS in professional soccer players.Methods: The subjects were 33 healthy professional soccer players. Players with a history of concussion were divided into two groups: a concussion group and a non-concussion group. The evaluation item was mBESS in the off-season. Statistical analysis was performed using Mann-Whitney U Test to compare the two groups (significance level: 5 %).Results: No significant differences were found in comparisons between groups (p＝0.523).Conclusion: No association was found between the presence of a history of concussion and mBESS in professional soccer players.